中国国有物资流通企业制度创新研究 = The reform of state-owned enterprise system of industrial materials trading firms in China - 计宁海 Ji, Ninghai (2008)
This study focus on the state-owned enterprises system of industrial materials trading firms. It points out that the reform on the trading firms has faced two fold issues: the ownership and operational system problems of state-owned enterprises; the problem of industrial boundary defined in the traditionally central-planned economic system. The empirical sfudy was conducted on the Coal Trading Company of Jiangsu Corporation of Industrial Materials Trading. Based on this study, some proposals of reforms on the enterprises system of the state-owned industrial materials trading firms are discussed.